221 Running pattern asymmetry evaluation after anterior cruciate ligament reconstruction could be a way to detect re-injuries. (3rd March 2020) - Rambaud, Alexandre; Neri, Thomas; Morin, Jean-Benoit; Philippot, Remi; Rossi, Jeremy; Samozino, Pierre; Edouard, Pascal
Abstract : Background: A test battery is recommended after anterior cruciate ligament reconstruction (ACLR) to help decision-making of return to sport (RTS). Running is important in RTS continuum, but it is currently not included in the usual test batteries. Could running pattern asymmetry, which can be observed after ACLR, be considered as a risk factor of ACL re-injuries? Objective: To analyse the interest of adding running pattern evaluation in test battery after ACLR. Design: Prospective cohort study. Setting : Patient with ACLR with Tegner score >6 and Marx Scale score >8 before first ACL injury. Patients (or Participants): 21 patients (12 women) with primary ACLR (graft type: Patellar (n=4) or Hamstring tendon (n=17)) without major chondral and/or meniscal lesion. Interventions (or assessment of risk factors): Running pattern evaluation was performed on a motorised instrumented treadmill in addition to recommended tests (questionnaires, knee laxity, Hop Tests and isokinetic evaluation) at 6 months after ACLR. ACL re-injuries were prospectively collected during the two years after ACLR, and comparisons between parameters were performed between ACLR patients who presented or not an ACL re-injury Main outcome measurements: Limb symmetry Index (LSI=operated leg/healthy leg x100) were calculated for running variables (Stride Length, Loading Rate, Leg Stiffness) and other parameters of test battery. Means were compared between groups. Results: Five patients had a re-injury (3 W/ 2 M), without significant differences in baseline characteristics (sport level, training frequency) with un-re-injured patients. For running variables, there was a significant difference for LSIs of Stride Length (Re-injury group 95.8±2.3% vs 99.0%±1.8%, p=0.003), Loading Rate (86.9±13.3% vs 98.3±9.6%, p=0.025), and Leg Stiffness (112.6±7.3% vs 103.7±8.0%, p=0.035), while there were no statistical differences for LSIs of other parameters of test battery. Conclusions: As greater running pattern asymmetry was reported in patients with ACL re-injury, this approach could be of interest for secondary prevention.